Calculation of oxidation depth in low-carbon steel under nonstationary conditions by introducing a fictitious time - Marija Riđošić; Branko Pejović; Milorad Tomić; Slavko Smiljanić (Zaštita Materijala)
Oxidation as an undesired phenomena particularly evident in and significant for low-carbon steel, occurs at elevated temperatures due to the chemical effects of the atmosphere. The exact information about the thickness of the oxidation layer has a great practical importance. The aim of this paper is to take the existing process for calculating the depth of oxidation, which is valid for a stationary area, and use it for a non-stationary area. The non-stationary area of the heating curve is devided into a number of segments in which medium temepratures are relevant. These medium temperatures were defined in the paper. In order to use the effect of oxidation of the previous segment on the proceeding segment, a fictitious time was introduced, considering the temperature of the next segment. In the process of calculating the main relation, the starting point were individual, specific solutions, based on which we obtained the general solutions for the problem. The proposed model was illustrated using a suitable example where the depth of oxidation was determined for a typical low-carbon steel under atmospheric conditions, both for the stationary and for the non-stationary area.